Biharmonic and biconservative submanifolds of lorentizan space forms - Kayhan, Aykut (Graduate School, 2022)
In 1964, Eells and Sampson gave the definition of biharmonic maps as a generalization of harmonic maps during they were studying on the energy functional E between Riemannian manifolds which has geometrical and physical interest. Later, many geometers interested in biharmonic maps. By the definition, a biharmonic map φ : M → N between two Semi-Riemannian manifolds is a critical point of the bienergy functional E2(φ) = 1 2 Z M ∥τ(φ)∥ 2 vg, where τ(φ) = trace∇dφ is the tension field of φ that vanishes for harmonic maps. If φ is a biharmonic isometric immersion into N then M is said to be biharmonic submanifold of N. In the middle of 1980's, Chen studied biharmonic submanifolds in Euclidean spaces as a part of his program of understanding finite type submanifolds in Euclidean spaces. He gave an alternative definition of biharmonic submanifolds in Euclidean spaces. That definition is also same for pseudo-Euclidean spaces: If the position vector field x : M → E n satisfies ∆ 2 x = 0 then M is called biharmonic submanifold, where ∆ denote the Laplacian of M. By the well known Laplace-Beltrami identity this equation is equivalent to ∆H = 0, where H is the mean curvature vector of M. In the mean time, independently, Jiang showed that a smooth map φ is biharmonic if and only if its bitension field τ2(φ) (which corresponds the Euler-Lagrange equation of bienergy functional) vanishes identically, i.e., τ2(φ) = 0. Jiang also showed that τ2(φ) = 0 if and only if ∆H = 0 for an isometric immersion φ : M → E n . As a result, definitions given by Chen and Jiang coincide for the class of Euclidean and pseudo-Euclidean submanifolds. Biconservative submanifolds arose from the theory of biharmonic submanifolds. Stress-energy tensor for the energy function described by Hilbert was expanded for the bienergy function as follows S2(X,Y) = 1 2 ∥τ(φ)∥ 2 ⟨X,Y⟩+⟨dφ,∇τ(φ)⟩⟨X,Y⟩ −⟨dφ(X),∇Y τ(φ)⟩ − ⟨dφ(Y),∇Xτ(φ)⟩ xxi satisfying divS2 = −⟨τ2(φ),dφ⟩ . In general, a submanifold is called biconservative if divS2 = 0. It means (τ2(φ))T = 0. Indeed, this is equivalent to (∆H) T = 0 when the ambient space is pseudo-Euclidean. Because, for the isometric immersion into E n 1 , τ(φ) = −mH and τ2(φ) = m∆H. In this thesis we study on the biconservative submanifolds and biconservative hypersurfaces of the Lorentzian space forms and we also obtained some results related biharmonic ones. This work consists of seven sections and these sections were planned as follows: In the first section, we give a brief history and philosophy of biharmonic and biconservative submanifolds and studies has been done so far. In the second section, we give some basic notions of the submanifold theory on Lorentzian inner product space and biharmonic submanifolds. In the third section, biconservative surfaces with constant mean curvature (CMC) in Minkowski 4-space E 4 1 is studied. Firstly, we determine the canonical forms of the shape operator and then we give some examples of such submanifolds in E 4 1 . Later, we classify biconservative CMC submanifolds in E 4 1 . Then, we generalize all results to the CMC surfaces of S 4 1 and H4 1 . In the fourth section, we examine the biconservative hypersurfaces in Minkowski 4-space E 4 1 . In particular, we study hypersurfaces with non-diagonalizable shape operator A satisfying A(∇H) = − nH 2 ∇H, where n and H are the dimension and the mean curvature of the hypersurface, respectively. We determine the canonical forms of the shape operator, the mean curvature, sectional curvature and Levi-Civita connection of this hypersurface. Afterwards we give the necessary and sufficient condition for this hypersurface to be biconservative. Later we classify the biconservative hypersurface in E 4 1 and show the uniquniess of them. In fifth section, we examine the biconservative hypersurfaces with certain shape operator in Minkowski 5 space E 5 1 . We give some non-existence theorems. In the sixth section, we examine the biconservative submanifolds with mean curvature whose gradient is light-like in E n 1 . We give some non-existence results. In the last section, the obtained conclusions are shared and recommendations are made about the future of the problems.
Lorentz uzay formlarının biharmonik ve bikonservatif altmanifoldları
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2022
Keywords: Lorentizan space forms; Lorentz uzay formları; Biconservative submanifolds; Bikonservatif altmanifoldları